Development and Effectiveness of a K3LH E-Module to Improve Learning Outcomes and Industrial Work Culture in Vocational Education - Ahmad Anwar; Sudiyono; Sunyoto; Andri Setiyawan; Febrian Arif Budiman (Rekayasa, 2025)
Occupational Health, Safety, Environment, and Industrial Work Culture learning in vocational schools is often constrained by limited interactive teaching materials, resulting in low student engagement and suboptimal learning outcomes. This condition highlights the urgent need for innovative digital learning resources that align with industrial demands and vocational student characteristics. This study aimed to design, develop, and evaluate the effectiveness of a K3LH E-Module for vocational education students. The research employed a Research and Development approach using the 4D development model, consisting of define, design, develop, and disseminate stages. The research subjects were 60 tenth-grade students of the Automotive Engineering program at Vocational High School in Semarang. Effectiveness testing was conducted at the classroom scale using an experimental group and a control group. Data were collected through expert validation sheets, practicality questionnaires, and pretest–posttest assessments. The results showed that the E-Module was highly feasible, with media expert validation reaching 89.5% and material expert validation 88.9%. Practicality testing indicated a very practical category with a score of 91.3%. Effectiveness analysis using N-Gain yielded a score of 58%, categorised as sufficiently effective. These findings demonstrate that the developed E-Module enhances student learning outcomes and promotes more active participation in K3LH learning. In conclusion, the K3LH E-Module is feasible, practical, and sufficiently effective for use as a digital learning resource in vocational education, with potential for further optimisation to improve learning gains.